Resin composition
By compounding specific components in the base polymer of polyethylene resin from biomass resources, the problem of poor shape of eye squid and pellets during melt forming process is solved, and the appearance optimization of the molded product is achieved.
Patent Information
- Application Number
- CN202180055399.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-31
- Filing Date
- 2021-08-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-08-26
AI Technical Summary
Polyethylene resins from biomass resources are prone to form fogs during the melt forming process, resulting in a decrease in appearance of the molded object and poor shape of the pellets, which affects the quality of processing and forming.
By mixing specific components in the base polymer of low-density biopolyethylene resin and ethylene-vinyl alcohol copolymer, such as ethylene-vinyl acetate copolymer, acid-modified polymer, and ethylene-vinyl alcohol copolymer with an ethylene content of 70 to 90 mol % by adjusting the composition ratio of the resin composition to suppress vitiligo and improve the shape of the pellets.
It effectively suppresses the occurrence and discoloration of the eye during molding, improves the shape of the pellets, and improves the appearance quality of the molded object.
Smart Images

Figure GDA0004113241260000231 
Figure GDA0004113241260000241
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, and more particularly to a resin composition that suppresses the occurrence of eye mucus even when a bio-polyethylene resin is used and can provide a molded product having an excellent appearance. Background Art
[0002] In the past, ethylene-vinyl alcohol copolymers have been mainly used as food packaging materials due to their excellent gas barrier properties and transparency. Sheets, films, etc. used as the above-mentioned food packaging materials can be made from the above-mentioned ethylene-vinyl alcohol copolymers alone, but are usually used as a multilayer structure formed by laminating polyolefin resins, etc. through melt molding via an adhesive layer in order to impart water resistance, strength, and other functions.
[0003] On the other hand, in recent years, in order to reduce environmental load, studies have been conducted to replace part of the resin used in the multilayer structure from petroleum-derived resins with resins derived from biomass resources such as plants (see, for example, Patent Documents 1 to 3).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-200968
[0007] Patent Document 2: Japanese Patent Application Publication No. 2014-104729
[0008] Patent Document 3: Japanese Patent Application Publication No. 2014-213903 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] The above-mentioned polyethylene resin derived from biomass resources contains many low molecular weight components compared with polyethylene resin derived from petroleum. Therefore, when a resin composition containing ethylene-vinyl alcohol copolymer and polyethylene resin derived from biomass resources is melt-molded, the polyethylene resin derived from biomass resources is sometimes rejected from the resin composition as eye mucus at the discharge port of a mixer, etc. The discoloration and eye mucus derived from the polyethylene resin increase according to the type and amount of polyethylene resin derived from biomass resources used in the resin composition, and the appearance is reduced, so further improvement is sought.
[0011] In addition, in the case of pellets manufactured by resin combination, usually, the melt-kneaded resin combination is extruded and cut to manufacture in a strand shape, but in the case of large surface roughness during extrusion, it becomes difficult to cut, and it is easy to become a pellet with a bad shape. The pellets with the above-mentioned bad shape become the cause of the gel generation during film making caused by the bad bite-in and the increase of micropowder during processing and forming, and therefore, the pellet shape is important. However, in the case of pellets manufactured by the resin combination comprising the polyethylene resin of the biomass resource source, the surface roughness during extrusion is large, and it is easy to become a pellet with a bad shape, therefore, further improvement is sought.
[0012] Solutions for solving problems
[0013] The present inventors conducted intensive studies in view of the above-mentioned actual situation and found that the above-mentioned problems can be solved by blending specific components into a base polymer comprising a low-density bio-polyethylene resin and an ethylene-vinyl alcohol copolymer having an ethylene content of 20 to 60 mol % at a specific ratio.
[0014] That is, the present invention provides the following [1] and [2].
[0015] [1] A resin composition comprising: a low-density bio-based polyethylene resin (A); an ethylene-vinyl alcohol copolymer having an ethylene content of 20 to 60 mol % (B); and at least one component (C) selected from the group consisting of ethylene-vinyl acetate copolymers, acid-modified polymers, and ethylene-vinyl alcohol copolymers having an ethylene content of 70 to 90 mol %, wherein the low-density bio-based polyethylene resin (A) is a low-density bio-based polyethylene resin other than a linear low-density bio-based polyethylene resin, and the weight ratio of the component (A) to the component (B) [(A) / (B)] is 10 / 90 to 49 / 51.
[0016] [2] The resin composition according to [1], wherein the content of the component (C) is 0.1 to 20 parts by weight relative to 100 parts by weight of the total of the component (A) and the component (B).
[0017] Effects of the Invention
[0018] The resin composition of the present invention can suppress the deterioration of the pellet shape, suppress the occurrence of eye discharge during molding, and suppress the deterioration of the appearance of the molded product such as discoloration. DETAILED DESCRIPTION
[0019] Hereinafter, although the form for implementing this invention is demonstrated concretely, this invention is not limited to these.
[0020] In the present invention, an "ethylene-vinyl alcohol copolymer having an ethylene content of 20 to 60 mol %" may be referred to as "EVOH".
[0021] In addition, in the present invention, "x and / or y (x, y are arbitrary structures or components)" means only x, only y, and a combination of three types of x and y.
[0022] The resin composition of the present invention is prepared by blending a specific component (C) into a base polymer comprising a low-density bio-polyethylene resin (A) and EVOH (B) at a specific ratio. Each component will be described below.
[0023] <Low-density bio-polyethylene resin (A)>
[0024] The low-density bio-based polyethylene resin (A) used in the present invention is a linear low-density bio-based polyethylene resin (LLDPE, density 0.910-0.925 g / cm 3 ) other than low-density bio-polyethylene resins (LDPE, density less than 0.925 g / cm 3 ).
[0025] The above-mentioned "bio-polyethylene resin" refers to a polyethylene resin obtained by chemical or biological synthesis using renewable biomass resources as raw materials. The above-mentioned bio-polyethylene resin has the following characteristics: when it is incinerated, the carbon dioxide concentration in the atmosphere will not increase due to the carbon neutrality of biomass.
[0026] The bio-polyethylene resin preferably uses plant-derived ethylene derived from bioethanol obtained from plant raw materials. That is, the bio-polyethylene resin is preferably a plant-derived polyethylene resin.
[0027] There is no difference in physical properties such as molecular weight, mechanical properties and thermal properties between polyethylene resins derived from plants (biomass resources) and polyethylene resins derived from petroleum. Therefore, in order to distinguish between them, the biomass degree is usually used. The above biomass degree refers to: the carbon content of polyethylene resins derived from petroleum does not contain 14 C (radiocarbon 14, half-life 5730 years), so the accelerator mass analysis was used to determine the 14 The concentration of C is used as an indicator of the content ratio of the plant-derived bio-polyethylene resin. Therefore, if the film is made of a plant-derived polyethylene resin, when the biomass of the film is measured, the biomass is in accordance with the content of the plant-derived polyethylene resin. That is, the bio-polyethylene resin is characterized in that it contains radioactive carbon ( 14 C).
[0028] The biomass content can be measured, for example, by the following method. The sample to be measured is burned to generate carbon dioxide, and the carbon dioxide purified in a vacuum line is reduced with hydrogen using iron as a catalyst to generate graphite. The graphite is then installed in a tandem accelerator. 14 C-AMS dedicated device (manufactured by NEC Corporation) 14 The count of C, 13 The concentration of C 13 C / 12 C) 14 The concentration of C 14 C / 12 C) is measured, and the carbon content of the sample relative to the modern carbon standard is calculated from the measured value. 14 The ratio of C concentration.
[0029] As the low-density bio-polyethylene resin (A), for example, there can be mentioned: a low-density bio-polyethylene homopolymer and a low-density bio-polyethylene copolymer obtained by polymerizing ethylene derived from bioethanol. The low-density bio-polyethylene copolymer is a copolymer of ethylene and a small amount of comonomer, for example, ethylene and other α-olefin monomers with a weight fraction of less than 50%, or a non-olefin monomer with a functional group with a weight fraction of less than 3%.
[0030] Examples of the other α-olefins include α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-ene; 1-ethyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, etc. These can be used alone or in combination of two or more.
[0031] Examples of the non-olefin monomer include styrene monomers, diene monomers, cyclic monomers, oxygen atom-containing monomers, etc. These can be used alone or in combination of two or more.
[0032] Examples of the styrene-based monomer include styrene, 4-methylstyrene, and 4-dimethylaminostyrene.
[0033] Examples of the diene monomers include 1,3-butadiene, 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 1,4-octadiene, 1,5-octadiene, 1,6-octadiene, 1,7-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, 4-ethylidene-8-methyl-1,7-nonadiene, 4,8-dimethyl-1,4,8-decatriene (DMDT), dicyclopentadiene, cyclohexadiene, and dicyclooctadiene.
[0034] Examples of the cyclic monomer include methylene norbornene, 5-vinyl norbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,2-norbornadiene, and cyclopentene.
[0035] Examples of the oxygen atom-containing monomer include hexenol, hexenoic acid, and methyl octenoate.
[0036] The above-mentioned other α-olefins and non-olefin monomers can use renewable biomass resources as raw materials, or can use petroleum as raw materials. When using renewable biomass resources as raw materials, the biomass degree of the final product can be further improved. In addition, when using petroleum as raw materials, various substances can be obtained, and therefore, by using them to manufacture, the physical properties of the low-density bio-polyethylene resin (A) can be easily adjusted.
[0037] The low-density bio-polyethylene resin (A) used in the present invention can be obtained, for example, by homopolymerizing ethylene or copolymerizing ethylene with a comonomer using a metallocene catalyst or a Ziegler-Natta catalyst according to a conventional method, wherein the metallocene catalyst is preferably used.
[0038] The melt flow rate (MFR) (190°C, load 2160 g) of the low-density bio-polyethylene resin (A) is usually 0.1 to 50 g / 10 min, preferably 0.5 to 30 g / 10 min, particularly preferably 2 to 10 g / 10 min.
[0039] When the MFR is too large, the film forming properties tend to become unstable, and when it is too small, the viscosity becomes excessively high, and melt extrusion tends to become difficult.
[0040] Examples of commercially available products of the low-density bio-polyethylene resin (A) that can be preferably used in the present invention include SEB853 (manufactured by Braskem).
[0041] The low-density bioethylene-based resin (A) may be used alone or in combination of two or more.
[0042] <EVOH(B)>
[0043] The EVOH (B) is a resin obtained by saponifying an ethylene-vinyl ester copolymer, which is a copolymer of ethylene and a vinyl ester monomer, and is a water-insoluble thermoplastic resin. As the vinyl ester monomer, vinyl acetate is generally used from an economical point of view.
[0044] As the polymerization method of ethylene and vinyl ester monomers, any known polymerization method such as solution polymerization, suspension polymerization, and emulsion polymerization can be used, and solution polymerization using methanol as a solvent is usually used. The saponification of the obtained ethylene-vinyl ester copolymer can also be carried out by a known method.
[0045] The EVOH (B) produced in this way mainly contains structural units derived from ethylene and vinyl alcohol structural units, and usually contains a small amount of vinyl ester structural units remaining without being saponified.
[0046] As the vinyl ester monomer, vinyl acetate is typically used from the viewpoint of market availability and good impurity treatment efficiency during production. As other vinyl ester monomers other than the vinyl acetate, for example, aliphatic vinyl esters such as vinyl formate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, vinyl stearate, and vinyl versatate, and aromatic vinyl esters such as vinyl benzoate can be mentioned. Usually, aliphatic vinyl esters having 3 to 20 carbon atoms, preferably 4 to 10 carbon atoms, and particularly preferably 4 to 7 carbon atoms can be used. These can be used alone or in combination of two or more.
[0047] The ethylene content in the EVOH (B) can be controlled by the ethylene pressure when copolymerizing the vinyl ester monomer and ethylene, and is 20 to 60 mol%, preferably 25 to 50 mol%, and particularly preferably 25 to 35 mol%. When the above content is too low, the gas barrier properties and melt moldability under high humidity tend to be reduced, and conversely, when it is too high, the gas barrier properties tend to be reduced.
[0048] In addition, the said ethylene content can be measured based on ISO14663.
[0049] The saponification degree of the vinyl ester component in EVOH (B) can be controlled by the amount of the saponification catalyst (usually a basic catalyst such as sodium hydroxide is used) when saponifying the ethylene-vinyl ester copolymer, the temperature, the time, etc., and is usually 90 to 100 mol%, preferably 95 to 100 mol%, and particularly preferably 99 to 100 mol%. When the saponification degree is too low, there is a tendency for gas barrier properties, thermal stability, moisture resistance, etc. to be reduced.
[0050] The saponification degree of the EVOH (B) can be measured in accordance with JIS K6726 (wherein EVOH is used as a solution uniformly dissolved in a water / methanol solvent).
[0051] The melt flow rate (MFR) (210°C, load 2160 g) of the EVOH (B) is usually 0.5 to 100 g / 10 min, preferably 1 to 50 g / 10 min, and particularly preferably 3 to 35 g / 10 min. If the MFR is too large, the film forming properties tend to become unstable, while if it is too small, the viscosity tends to become excessively high, making melt extrusion difficult.
[0052] The MFR is an index of the degree of polymerization of EVOH, and can be adjusted by the amount of the polymerization initiator and the amount of the solvent when ethylene and the vinyl ester monomer are copolymerized.
[0053] EVOH (B) may further contain a structural unit derived from the following comonomer within a range not impairing the effects of the present invention (for example, 10 mol% or less of EVOH).
[0054] Examples of the comonomer include olefins such as propylene, 1-butene, and isobutylene; hydroxyl-containing α-olefins such as 3-butene-1-ol, 3-butene-1,2-diol, 4-pentene-1-ol, and 5-hexene-1,2-diol, and their esters, acylates, and other derivatives; hydroxyalkyl vinylides such as 2-methylenepropane-1,3-diol and 3-methylenepentane-1,5-diol; 1,3-diacetoxy-2-methylenepropane, 1,3-dipropionyloxy-2-methylenepropane, Hydroxyalkyl vinylene diacetates such as methylpropane and 1,3-dibutyryloxy-2-methylenepropane; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, phthalic acid (anhydride), maleic acid (anhydride), itaconic acid (anhydride) or their salts, or mono- or di-alkyl esters having an alkyl group with 1 to 18 carbon atoms; acrylamide, N-alkyl acrylamide having an alkyl group with 1 to 18 carbon atoms, N,N-dimethylacrylamide, 2-acrylamidopropanesulfonic acid or its salts, acrylamidopropyl dimethylamine or its acid acrylamides such as methyl methacrylamide, N-alkyl methyl methacrylamide having an alkyl group with a carbon number of 1 to 18, N,N-dimethyl methyl methacrylamide, 2-methyl acrylamide propanesulfonic acid or its salt, methyl acrylamide propyl dimethylamine or its acid salt or its quaternary salt; N-vinyl amides such as N-vinyl pyrrolidone, N-vinyl formamide, N-vinylacetamide; acrylonitriles such as acrylonitrile and methacrylonitrile; vinyl ethers such as alkyl vinyl ether having an alkyl group with a carbon number of 1 to 18, hydroxyalkyl vinyl ether, alkoxyalkyl vinyl ether; halogenated vinyl compounds such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride, vinyl bromide; vinyl silanes such as trimethoxyvinylsilane; halogenated allyl ester compounds such as allyl acetate and allyl chloride; allyl alcohols such as allyl alcohol and dimethoxyallyl alcohol; comonomers such as (3-acrylamide-3-dimethylpropyl)-trimethylammonium chloride and acrylamide-2-methylpropanesulfonic acid. These can be used alone or in combination of two or more.
[0055] In particular, EVOH obtained by copolymerizing hydroxyl-containing α-olefins, that is, EVOH having a primary hydroxyl group in a side chain is preferred in that the gas barrier properties are maintained and the secondary moldability is improved. Among them, EVOH having a 1,2-diol structure in a side chain is preferred.
[0056] In particular, in the case of EVOH having a primary hydroxyl group in a side chain, the content of the structural unit derived from the monomer having the primary hydroxyl group is preferably generally 0.1 to 20 mol %, further 0.5 to 15 mol %, particularly 1 to 10 mol % of EVOH.
[0057] The EVOH (B) used in the present invention may be one that has been "post-modified" by urethanization, acetalization, cyanoethylation, oxyalkyleneization, or the like.
[0058] Furthermore, the EVOH (B) used in the present invention may be a mixture of two or more EVOH (B), for example, EVOH (B) having different saponification degrees, polymerization degrees, copolymer components, etc.
[0059] The weight ratio of the low-density bio-polyethylene resin (A) to the EVOH (B) in the resin composition of the present invention is 10 / 90 to 49 / 51, preferably 20 / 80 to 45 / 55, and particularly preferably 30 / 70 to 40 / 60 from the perspective of suppressing the deterioration of the pellet shape. If the blending ratio of the low-density bio-polyethylene resin (A) is too small, the moldability at low temperatures is reduced. On the other hand, if the low-density bio-polyethylene resin (A) is too much, the pellet shape is deteriorated.
[0060] The base polymer in the resin composition of the present invention is a low-density bio-polyethylene resin (A) and EVOH (B), and the content of the base polymer in the resin composition is usually 60% by weight or more, preferably 70% by weight or more, and particularly preferably 80% by weight or more. In addition, the upper limit of the content of the base polymer is usually 99.9% by weight.
[0061] <Ingredient (C)>
[0062] In the present invention, at least one component (C) selected from the group consisting of ethylene-vinyl acetate copolymers, acid-modified polymers, and ethylene-vinyl alcohol copolymers having an ethylene content of 70 to 90 mol% is blended into the above-mentioned base polymer, thereby suppressing deterioration of the pellet shape and suppressing deterioration in appearance such as the occurrence of eye discharge during molding and discoloration of the molded product.
[0063] The content of the above-mentioned component (C) is preferably set to 0.1 to 20 parts by weight, more preferably 0.2 to 15 parts by weight, and particularly preferably 0.5 to 10 parts by weight relative to a total of 100 parts by weight of the low-density bio-polyethylene resin (A) and EVOH (B). By making the content of the component (C) within the above-mentioned range, there is a tendency to suppress the deterioration of the shape of the pellets, and also suppress the occurrence of eye mucus during molding, discoloration of the molded product, and other appearance reduction. In addition, when the resin composition contains two or more components (C), the sum of all contents is taken as the content of the component (C). Below, each component (C) is described in detail.
[0064] 〔Ethylene-vinyl acetate copolymer〕
[0065] The ethylene-vinyl acetate copolymer (hereinafter, sometimes referred to as "EVA") is a polymer obtained by copolymerizing ethylene and vinyl acetate. In addition, EVA may be modified as necessary.
[0066] The content of vinyl acetate in the above-mentioned EVA is usually 1 to 60 mol%, preferably 2 to 50 mol%, and particularly preferably 3 to 30 mol%. If the content of vinyl acetate is too low, there is a tendency that eye discharge is suppressed and the appearance improvement of the molded product becomes insufficient. On the contrary, if the content of vinyl acetate is too high, the decomposition temperature of EVA is low, and acetic acid is generated during decomposition, so there is a possibility of damaging mechanical properties. In addition, there is a tendency that the thermal stability of the resin composition itself is reduced.
[0067] The melt flow rate (MFR) of the EVA (190°C, load 2160g) is usually 0.1 to 100 g / 10 minutes, preferably 0.5 to 50 g / 10 minutes, and particularly preferably 1 to 30 g / 10 minutes. If the MFR is not within the above range, the compatibility with the base polymer tends to decrease, and the dispersibility during mixing tends to decrease.
[0068] The above-mentioned EVA can also be a modified body containing a carboxyl group obtained by chemically bonding an unsaturated carboxylic acid or anhydride thereof by addition reaction, grafting reaction, etc. within the scope that does not hinder the main purpose of the present invention. The above-mentioned modification amount is, for example, preferably less than 10 mol%. As the above-mentioned unsaturated carboxylic acid or anhydride thereof, for example, olefinic unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, ethacrylic acid, butene acid, fumaric acid, itaconic acid, citraconic acid, maleic acid, ethyl maleate, olefinic unsaturated dicarboxylic acids such as monomethyl maleate, monoethyl maleate, their anhydrides, half esters, etc. can be cited. Among them, maleic anhydride is preferred.
[0069] The content of the above-mentioned EVA is preferably set to 0.1 to 20 parts by weight, more preferably 0.2 to 15 parts by weight, and particularly preferably 0.5 to 10 parts by weight relative to a total of 100 parts by weight of the low-density bio-polyethylene resin (A) and EVOH (B). If the content of EVA is within the above-mentioned range, there is a tendency to further suppress the deterioration of the shape of the pellets, and to suppress the occurrence of eye mucus during molding, discoloration of the molded product, and other appearance reduction. In addition, the above-mentioned EVA can be used alone, or in combination with two or more EVAs having different ethylene content, molecular weight, MFR, density, modifying group, and modification amount thereof.
[0070] 〔Acid-modified polymer〕
[0071] The acid-modified polymer refers to a carboxyl group-containing modified product obtained by chemically bonding an unsaturated carboxylic acid or anhydride thereof to a polymer by an addition reaction, a graft reaction, or the like.
[0072] As the unsaturated carboxylic acid or its anhydride, for example, ethylenically unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, ethacrylic acid, and crotonic acid, ethylenically unsaturated dicarboxylic acids such as fumaric acid, itaconic acid, citraconic acid, maleic acid, monomethyl maleate, and monoethyl maleate, anhydrides thereof, half esters, etc. can be mentioned. These can be used alone or in combination of two or more.
[0073] Examples of the polymer include polyethylene, polypropylene, polybutene, and copolymers of ethylene and an α-olefin having 3 to 20 carbon atoms (ethylene-α-olefin copolymers).
[0074] As the acid-modified polymer used in the present invention, a maleic anhydride-modified polymer is preferred.
[0075] These maleic anhydride-modified polymers are described below.
[0076] [Maleic anhydride modified polymer]
[0077] The maleic anhydride-modified polymer is a polymer in which at least one of the main chain and the side chain is modified by maleic anhydride. The maleic anhydride-modified polymer excludes EVA modified by maleic anhydride and ethylene-vinyl alcohol copolymers with an ethylene content of 70 to 90 mol% modified by maleic anhydride.
[0078] Examples of the polymer modified with maleic anhydride include polyethylene, polypropylene, polybutene, and ethylene-α-olefin copolymers.
[0079] Among them, from the viewpoint of suppressing the occurrence of eye discharge, ethylene-α-olefin copolymers and polyethylene are preferred, and ethylene-α-olefin copolymers are particularly preferred.
[0080] Examples of the ethylene-α-olefin copolymer include ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-4-methyl-1-pentene copolymers, ethylene-1-octene copolymers, ethylene-1-butene-1-hexene copolymers, ethylene-1-butene-4-methyl-1-pentene copolymers, and ethylene-1-butene-1-octene copolymers. Preferred are ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-1-octene copolymers, ethylene-1-butene-1-hexene copolymers, and ethylene-1-butene-1-octene copolymers.
[0081] The maleic anhydride-modified polymer can be obtained by copolymerizing a part of monomers constituting the polymer in place of maleic anhydride, or by introducing maleic anhydride into a part of the side chain by a graft reaction such as radical addition.
[0082] The acid value of maleic anhydride modified polymer is usually below 50 mgKOH / g, preferably below 30 mgKOH / g, and particularly preferably below 20 mgKOH / g. If the acid value is too high, there is a tendency that the reaction sites with the hydroxyl groups in EVOH (B) increase, a high degree of polymerization product is generated during the melt kneading process, the stability during extrusion processing is reduced, and it is difficult to obtain a good molded product. It should be noted that the lower limit of the acid value is usually 1 mgKOH / g, preferably 2 mgKOH / g. In addition, the above acid value is measured based on JIS K0070.
[0083] When maleic anhydride-modified polyethylene is used as the maleic anhydride-modified polymer, the melt flow rate (MFR) (190°C, load 2160 g) is usually 0.01 to 150 g / 10 min, preferably 0.1 to 50 g / 10 min, more preferably 1 to 25 g / 10 min, further preferably 3 to 10 g / 10 min.
[0084] When a maleic anhydride-modified ethylene-α-olefin copolymer is used as the maleic anhydride-modified polymer, the MFR (230°C, load 2160 g) is usually 0.1 to 150 g / 10 min, preferably 0.5 to 100 g / 10 min, more preferably 1 to 50 g / 10 min, further preferably 5 to 35 g / 10 min.
[0085] If the MFR is outside the above range, the compatibility with the base polymer will decrease, and the dispersibility during mixing will tend to decrease.
[0086] The content of the maleic anhydride modified polymer is preferably 0.1 to 20 parts by weight, more preferably 0.2 to 15 parts by weight, and particularly preferably 0.5 to 10 parts by weight relative to a total of 100 parts by weight of the low-density bio-polyethylene resin (A) and EVOH (B). If the content of the maleic anhydride modified polymer is within the above range, there is a tendency to further suppress the deterioration of the pellet shape, and to suppress the occurrence of eye mucus during molding, discoloration of the molded product, and other appearance reduction. In addition, the maleic anhydride modified polymer can be used alone or in combination of two or more.
[0087] [Ethylene-vinyl alcohol copolymer containing 70 to 90 mol% of ethylene structural units]
[0088] The ethylene-vinyl alcohol copolymer having an ethylene structural unit content of 70 to 90 mol% (hereinafter sometimes referred to as "EVA saponified product") is obtained by saponifying the vinyl acetate component of an ethylene-vinyl acetate copolymer having an ethylene content of 70 to 90 mol%, and is different from the aforementioned EVA in terms of saponification.
[0089] The ethylene-vinyl acetate copolymer can be produced by any known polymerization method, such as solution polymerization, suspension polymerization, emulsion polymerization, etc., and the saponification of the ethylene-vinyl acetate copolymer can also be carried out by a known method. In addition, the EVA saponified product can be modified as needed.
[0090] The ethylene content of the EVA saponified product is 70 to 90 mol%, preferably 75 to 90 mol%, particularly preferably 80 to 90 mol%. If the ethylene content is too low, the effects of the present invention (such as eye discharge suppression) tend to be insufficient.
[0091] The saponification degree of the EVA saponified product is usually 20 mol% or more, more preferably 60 to 100 mol%, particularly preferably 90 to 100 mol%. That is, if the saponification degree is too low, the effects of the present invention (such as eye discharge suppression) may become insufficient.
[0092] The melt flow rate (MFR) (190°C, load 2160 g) of the EVA saponified product is usually 0.5 to 100 g / 10 min., more preferably 1 to 50 g / 10 min., particularly preferably 2 to 30 g / 10 min., in terms of excellent dispersibility and excellent effects of the present invention.
[0093] The above-mentioned EVA saponification product can also be a modified body obtained by chemically bonding an unsaturated carboxylic acid or its anhydride through addition reaction, grafting reaction, etc. within the scope that does not hinder the main purpose of the present invention. The above-mentioned modification amount is, for example, preferably less than 10 mol%. As the above-mentioned unsaturated carboxylic acid or its anhydride, for example, olefinic unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, ethacrylic acid, butene acid, fumaric acid, itaconic acid, citraconic acid, maleic acid, monomethyl maleate, monoethyl maleate, maleic anhydride, olefinic unsaturated dicarboxylic acids, their anhydrides, half esters, etc. can be cited. They can be used alone or in combination of two or more. Among them, maleic anhydride is preferred.
[0094] The content of the above-mentioned EVA saponified product is preferably set to 0.1 to 20 parts by weight, more preferably 0.2 to 15 parts by weight, and particularly preferably 0.5 to 10 parts by weight relative to a total of 100 parts by weight of the low-density bio-polyethylene resin (A) and EVOH (B). If the content of the EVA saponified product is within the above-mentioned range, there is a tendency to further suppress the deterioration of the shape of the pellets, and to suppress the occurrence of eye mucus during molding, discoloration of the molded product, and other appearance reduction. In addition, the above-mentioned EVA saponified product can be used alone, or in combination with two or more EVA saponified products having different ethylene content, saponification degree, molecular weight, MFR, density, modified group, and modification amount thereof.
[0095] The resin composition of the present invention contains the above-mentioned component (C) in the base polymer [low-density bio-polyethylene resin (A) + EVOH (B)], wherein the component (C) is preferably EVA or an acid-modified polymer, and more preferably EVA.
[0096] [Other ingredients]
[0097] The resin composition of the present invention may contain a thermoplastic resin (such as petroleum-derived polyethylene) other than the above (A) to (C) and an additive generally added to a thermoplastic resin, within a range not impairing the effects of the present invention.
[0098] Examples of the additives include plasticizers (for example, aliphatic polyols such as ethylene glycol, glycerol, and hexylene glycol), oxygen absorbers, heat stabilizers, light stabilizers, ultraviolet absorbers, colorants, antistatic agents, surfactants (excluding those used as lubricants), antibacterial agents, anti-blocking agents, fillers (for example, inorganic fillers), etc. These additives may be used alone or in combination of two or more.
[0099] [Manufacturing of resin composition]
[0100] The resin composition of the present invention comprises the above (A) to (C), and is preferably formed only from the above (A) to (C), or is formed only from the above (A) to (C) and the above other components as required. In addition, the above low-density bio-polyethylene resin (A) and EVOH (B) may be raw materials that have never been used for molding (unrecycled products), or may be recycled materials such as waste of multilayer structures having layers containing low-density bio-polyethylene resin (A) and EVOH (B) generated during the production of the multilayer structure product described later.
[0101] In addition, depending on the situation, the recycled materials of the multilayer structure used as various packaging materials can also be used. In general, the multilayer structure used as a packaging material for food, etc., in addition to the layer formed by the low-density bio-polyethylene resin (A) and EVOH (B), also includes an adhesive resin layer and a recycled material layer. Therefore, in the resin composition of the present invention, these adhesive resin layers and recycled material layers can be included within a range that does not hinder the effect of the present invention (for example, less than 30% by weight in the resin composition).
[0102] Hereinafter, the method for producing the resin composition of the present invention will be described using a recycled product of a multilayer structure including a layer composed of a low-density bio-polyethylene resin (A) and EVOH (B).
[0103] Unnecessary parts (scrap) such as scraps and ends generated during the production of multilayer structure products and recycled multilayer structure products collected as waste are usually pulverized and the particle size is adjusted using a sieve or the like as needed, and then used as a raw material for the resin composition of the present invention.
[0104] When the above-mentioned recyclate is pulverized, it can be carried out by using a known pulverizer. The apparent density of the pulverized product is usually 0.25 to 0.85 g / mL, more preferably 0.3 to 0.7 g / mL, and particularly preferably 0.35 to 0.6 g / mL. When the apparent density is too small, the dispersion of the low-density bio-polyethylene resin (A) in the resin composition layer becomes poor, and the melt moldability and mechanical properties of the resin composition layer of the obtained molded product tend to decrease. When the apparent density is too large, there is a tendency that the melt moldability of the recycled material layer of the obtained molded product decreases due to poor supply in the extruder. It should be noted that the above-mentioned apparent density is a value measured according to the "5.3 Apparent Density" test method of JIS K6891.
[0105] The above-mentioned apparent density can be controlled by arbitrarily adjusting the shape of the pulverizing blade of the pulverizer, the rotation speed of the pulverizing blade, the processing speed of pulverization, the aperture size of the mesh used as a sieve, etc. In addition, the shape and particle size of the pulverized product can be adjusted by a known method.
[0106] When a pulverized product of a multilayer structure containing a low-density bio-polyethylene resin (A) and EVOH (B) is used (hereinafter referred to as a "pulverized product"), the resin composition of the present invention is produced by adding component (C) to the pulverized product. From the perspective of productivity, unrecycled low-density bio-polyethylene resin (A) and unrecycled EVOH (B) may be blended into the pulverized product.
[0107] Examples of the method for producing the resin composition include known methods such as a dry blending method, a melt kneading method, a solution mixing method, and an impregnation method.
[0108] As the dry blending method, for example, the following can be mentioned: method (i), dry blending the pulverized product and component (C) using a tumbler, etc. In addition, when performing the dry blending, component (C) may be directly dry blended, or pellets of a thermoplastic resin containing component (C) may be prepared in advance and the pellets of the thermoplastic resin may be dry blended with the pulverized product.
[0109] Examples of the melt kneading method include the following methods: method (ii) of melt kneading the dry blend of (i) above; method (iii) of adding component (C) to the pulverized product in a molten state and melt kneading the mixture; and the like.
[0110] Examples of the solution mixing method include the following methods: method (iv), in which a solution is prepared using the pulverized product, component (C) is added thereto, and after solidification and molding, solid-liquid separation and drying are performed; etc.
[0111] In the present invention, the above-mentioned different methods may be combined. Among them, the melt kneading method is preferred in terms of productivity, and the method (ii) is particularly preferred.
[0112] It should be noted that the resin composition of the present invention is not limited to the case where the recycled product of the multilayer structure is used as a raw material as described above, and low-density bio-polyethylene resin (A) and EVOH (B) which are not recycled products may also be used. When using unrecycled products, the resin composition may be prepared in a manner having the compounding composition of the present invention by a known general method, such as a dry blending method, a melt kneading method, a solution mixing method, etc., and the resin composition prepared in this way is also included in the present invention.
[0113] The YI (yellowness index) (ASTM D1925) of the resin composition of the present invention is usually 20 or less, preferably 15 or less, and particularly preferably 10 or less. The YI of the resin composition can be measured using a spectrocolorimeter (CM-3500d, manufactured by Konica Minolta, Inc.) under the following measurement conditions.
[0114] [Measurement conditions]
[0115] Light source: D65
[0116] CM-A120 White Calibration Plate
[0117] Use CM-A126 Petri Dish Set
[0118] ·Specular reflection measurement SCE
[0119] ·Measurement diameter:
[0120] The biomass content of the resin composition of the present invention is usually 10 to 90% by weight, preferably 15 to 70% by weight, and particularly preferably 20 to 50% by weight. The biomass content of the resin composition is calculated according to the following formula.
[0121] Biomass degree (weight %) = M1 / M2×100
[0122] In the above formula, M1 is the total weight of the low-density bio-polyethylene resin (A) used, and M2 is the total weight of the resin used.
[0123] The resin composition of the present invention has a melt flow rate (MFR) (210° C., load 2160 g) of usually 0.1 to 50 g / 10 min, preferably 0.5 to 30 g / 10 min, particularly preferably 2 to 10 g / 10 min.
[0124] The water content of the resin composition of the present invention is usually 0.01 to 0.5% by weight, preferably 0.02 to 0.35% by weight, and particularly preferably 0.05 to 0.3% by weight.
[0125] In addition, the water content of the resin composition in the present invention is measured / calculated according to the following method.
[0126] The weight of the resin composition before drying (W1) was measured on an electronic balance, dried in a hot air dryer at 150°C for 5 hours, and weighed after natural cooling in the dryer for 30 minutes (W2), and calculated according to the following formula.
[0127] Water content (weight %) = [(W1-W2) / W1] × 100
[0128] The resin composition of the present invention is prepared as a resin composition in various forms such as pellets and powders, and is provided as a molding material for various molded products. In particular, in the present invention, when provided as a material for melt molding, there is a tendency to more effectively obtain the effects of the present invention and it is preferred.
[0129] The molded article can be put into practical use as a multilayer structure having a layer molded using the resin composition of the present invention, typified by a single-layer film molded using the resin composition of the present invention.
[0130] [Multilayer structure]
[0131] The multilayer structure comprises a layer formed from the resin composition of the present invention. The layer formed from the resin composition of the present invention (hereinafter referred to as "resin composition layer") can be further provided with strength or other functions by laminating with another substrate (hereinafter referred to as "substrate resin") having a thermoplastic resin other than the resin composition of the present invention as a main component.
[0132] Examples of the base resin include linear low-density polyethylene, low-density polyethylene, ultra-low-density polyethylene, medium-density polyethylene, high-density polyethylene, polyethylene resins such as ethylene-propylene (block and random) copolymers and ethylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers, polypropylene resins such as polypropylene and propylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers, polybutylene, polypentene, polycyclic olefin resins (polymers having a cyclic olefin structure in at least one of the main chain and the side chain), and (unmodified) polyolefin resins. Unsaturated carboxylic acid-modified polyolefin resins obtained by graft modification with saturated carboxylic acids or their esters include polyolefin resins in a broad sense of modified olefin resins, ionomers, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-acrylic acid ester copolymers, polyester resins, polyamide resins (including copolymerized polyamides), polyvinyl chloride, polyvinylidene chloride, acrylic resins, polystyrene resins, vinyl ester resins, polyester elastomers, polyurethane elastomers, polystyrene elastomers, chlorinated polyethylene, chlorinated polypropylene and other halogenated polyolefins, aromatic or aliphatic polyketones, and the like.
[0133] Among them, in terms of economy and productivity, polyamide resins, polyolefin resins, polyester resins, and polystyrene resins are preferred, and polyethylene resins, polypropylene resins, polycyclic olefin resins, and polyolefin resins such as unsaturated carboxylic acid-modified polyolefin resins thereof are more preferred.
[0134] When the resin composition layer is set to a (a1, a2, ...) and the substrate resin layer is set to b (b1, b2, ...), the layer structure of the multilayer structure can be any combination of a / b, b / a / b, a / b / a, a1 / a2 / b, a / b1 / b2, b2 / b1 / a / b1 / b2, b2 / b1 / a / b1 / a / b1 / b2, etc. In addition, a recycling layer containing a mixture of the resin composition of the present invention and the substrate resin obtained by remelting and molding the ends, defective products, etc. generated in the process of manufacturing the multilayer structure can be provided. The number of layers of the multilayer structure is calculated as a cumulative number, usually 2 to 15, preferably 3 to 10. In the above-mentioned layer structure, an adhesive resin layer containing an adhesive resin can be sandwiched between each layer as needed.
[0135] As the above-mentioned adhesive resin, a known one can be used, and it can be appropriately selected according to the type of thermoplastic resin used in the substrate resin layer "b". Representative examples include modified polyolefin polymers containing carboxyl groups obtained by chemically bonding unsaturated carboxylic acids or their anhydrides to polyolefin resins through addition reactions, grafting reactions, etc. As the above-mentioned modified polyolefin polymers containing carboxyl groups, for example, maleic anhydride grafted modified polyethylene, maleic anhydride grafted modified polypropylene, maleic anhydride grafted modified ethylene-propylene (block and random) copolymers, maleic anhydride grafted modified ethylene-ethyl acrylate copolymers, maleic anhydride grafted modified ethylene-vinyl acetate copolymers, maleic anhydride modified polycyclic olefin resins, maleic anhydride grafted modified polyolefin resins, etc. can be cited. In addition, a mixture of one or more of them can be used.
[0136] When an adhesive resin layer is used between the resin composition layer and the base resin layer in the multilayer structure, the adhesive resin layers are located on both sides of the resin composition layer. Therefore, it is preferable to use an adhesive resin having excellent hydrophobicity.
[0137] The above-mentioned base resin and adhesive resin may contain conventionally known plasticizers, fillers, clays (montmorillonite, etc.), colorants, antioxidants, antistatic agents, lubricants, nucleating materials, anti-blocking agents, waxes, etc. within a range that does not hinder the main purpose of the present invention (for example, 30% by weight or less, preferably 10% by weight or less, relative to the entire resin).
[0138] The lamination of the resin composition of the present invention with the above-mentioned substrate resin (including the case where an adhesive resin layer is sandwiched) can be carried out by a known method. For example, the following methods can be cited: a method of melt-extrusion laminating the substrate resin to a film, sheet, etc. of the resin composition of the present invention; a method of melt-extrusion laminating the resin composition of the present invention to a substrate resin layer; a method of co-extruding the resin composition and the substrate resin; a method of dry laminating the resin composition layer and the substrate resin layer using a known adhesive such as an organic titanium compound, an isocyanate compound, a polyester compound, a polyurethane compound, etc.; a method of removing the solvent after applying a solution of the resin composition on the substrate resin; etc. Among them, from the perspective of cost and environment, the method of co-extruding the resin composition and the substrate resin is preferred.
[0139] The multilayer structure is subjected to (heating) stretching treatment as required. The stretching treatment may be either uniaxial stretching or biaxial stretching. In the case of biaxial stretching, it may be simultaneous stretching or sequential stretching. In addition, as a stretching method, a roller stretching method, a tenter stretching method, a tubular stretching method, a stretch blow molding method, a vacuum pressure forming method, etc., which have a high stretching ratio, may be adopted. The stretching temperature can be selected from a range of usually 40 to 170°C, preferably about 60 to 160°C, at a temperature near the melting point of the multilayer structure. When the stretching temperature is too low, the stretchability becomes poor, and when it is too high, it becomes difficult to maintain a stable stretched state.
[0140] It should be noted that after stretching, heat setting can be performed to impart dimensional stability. Heat setting can be performed by known means, for example, while maintaining the stretched film in a tensioned state, heat treatment is performed at usually 80 to 180° C., preferably 100 to 165° C., for usually 2 to 600 seconds. In addition, when a multilayer stretched film obtained from the resin composition of the present invention is used as a shrink film, in order to impart heat shrinkage, for example, a treatment such as blowing cold air to cool and fix the stretched film can be performed without performing the above-mentioned heat setting.
[0141] In addition, depending on the situation, the above-mentioned multilayer structure can also be used to obtain a cup or tray-shaped multilayer container. In this case, a conventional drawing molding method is generally used, and specific examples include vacuum molding, pressure molding, vacuum pressure molding, and plug-assisted vacuum pressure molding. In the case of obtaining a tube or bottle-shaped multilayer container (laminated structure) from a multilayer preform (a hollow tubular preform before blow molding), a blow molding method is used. Specifically, extrusion blow molding (double-head type, mold moving type, preform displacement type, rotary type, heat storage type, horizontal preform type, etc.), cold preform blow molding, injection blow molding, biaxial stretch blow molding (extrusion type cold preform biaxial stretch blow molding, injection type cold preform biaxial stretch blow molding, injection molding online biaxial stretch blow molding, etc.) and the like can be cited. The obtained laminate may be subjected to heat treatment, cooling treatment, calendaring treatment, printing treatment, dry lamination treatment, solution or melt coating treatment, bag making processing, deep drawing processing, box processing, tube processing, pyrolysis processing, etc. as necessary.
[0142] The thickness of the multilayer structure (including stretched ones), the thickness of the resin composition layer, the base resin layer and the adhesive resin layer further constituting the multilayer structure cannot be generalized depending on the layer constitution, the type of base resin, the type of adhesive resin, the application, the packaging form, the required physical properties, etc., but the thickness of the multilayer structure (including stretched ones) is usually 10 to 5000 μm, preferably 30 to 3000 μm, and particularly preferably 50 to 2000 μm. The resin composition layer is usually 1 to 500 μm, preferably 3 to 300 μm, and particularly preferably 5 to 200 μm, the base resin layer is usually 5 to 3000 μm, preferably 10 to 2000 μm, and particularly preferably 20 to 1000 μm, and the adhesive resin layer is usually 0.5 to 250 μm, preferably 1 to 150 μm, and particularly preferably 3 to 100 μm.
[0143] Furthermore, the thickness ratio of the resin composition layer to the substrate resin layer in the multilayer structure (resin composition layer / substrate resin layer), when there are multiple layers, is generally 1 / 99 to 50 / 50, preferably 5 / 95 to 45 / 55, and particularly preferably 10 / 90 to 40 / 60, as measured by the ratio of the thickest layers. In addition, the thickness ratio of the resin composition layer to the adhesive resin layer in the multilayer structure (resin composition layer / adhesive resin layer), when there are multiple layers, is generally 10 / 90 to 99 / 1, preferably 20 / 80 to 95 / 5, and particularly preferably 50 / 50 to 90 / 10, as measured by the ratio of the thickest layers.
[0144] Bags formed from the films, sheets, and stretched films obtained above, and containers formed from cups, trays, tubes, bottles, and the like are useful as packaging material containers for various types of food, including condiments such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oils, beverages, cosmetics, and medicines.
[0145] Example
[0146] The present invention will be described in more detail below by giving examples, but the present invention is not limited to the following examples unless the gist of the invention is exceeded. It should be noted that, unless otherwise specified, the following "parts" and "%" are by weight.
[0147] Prior to the examples, the following ingredients were prepared.
[0148] <Low-density bio-polyethylene resin (A)>
[0149] (A-1): Low-density bio-polyethylene [SEB853 (Green PE manufactured by Braskem), MFR 2.7 g / 10 min (190°C, load 2160 g), minimum biomass content 95% (plant-derived)]
[0150] (A'-1): Linear low-density bio-polyethylene [SLH118 (Green PE manufactured by Braskem), MFR 1.0 g / 10 min (190°C, load 2160 g), minimum biomass content 84% (plant-derived)]
[0151] (A'-2): High-density bio-polyethylene [SGM9450F (Green PE manufactured by Braskem), MFR 0.33 g / 10 min (190°C, load 5000 g), minimum biomass content 96% (plant-derived)]
[0152] (A'-3): Petroleum-derived polyethylene [NOVATEC LF448K1 (manufactured by Japan Polyethylene Corporation), MFR 2.0 g / 10 min (190° C., load 2160 g)]
[0153] <EVOH(B)>
[0154] (B-1): Ethylene vinyl alcohol copolymer [ethylene content: 29 mol%, MFR: 4 g / 10 min (210°C, load: 2160 g)]
[0155] (B-2): Ethylene vinyl alcohol copolymer [ethylene content: 32 mol%, MFR: 3 g / 10 min (210°C, load: 2160 g)]
[0156] (B-3): Ethylene vinyl alcohol copolymer [ethylene content: 38 mol%, MFR: 3 g / 10 min (210°C, load: 2160 g)]
[0157] (B-4): Ethylene vinyl alcohol copolymer [ethylene content 44 mol%, MFR 3 g / 10 min (210°C, load 2160 g)]
[0158] <Ingredient (C)>
[0159] 〔EVA〕
[0160] (C-1): EVA [Ultrathene 3B53A (manufactured by Tosoh Corporation), vinyl acetate content 25 mol%, MFR 5.3 g / 10 min (190° C., load 2160 g)]
[0161] 〔Acid-modified polymer〕
[0162] (C-2): Maleic anhydride-modified ethylene-α-olefin copolymer [acid-modified TAFMER MA8510 (manufactured by Mitsui Chemical Inc.), MFR 5.0 g / 10 min (230° C., load 2160 g)]
[0163] 〔EVA saponification〕
[0164] (C-3): EVA saponified product [Melthene H0051K (manufactured by Tosoh Corporation), vinyl acetate content 11 mol%, MFR 6.5 g / 10 min (190° C., load 2160 g)]
[0165] The above components were mixed at once in a dry blending manner according to the following Tables 1 and 2, and then fed to a twin-screw kneader at a rate of 25 kg / hour using a weight feeder, and then the strands were cut in a drum pelletizer to prepare pelletized resin compositions of Examples 1 to 15, Comparative Examples 1 to 7, and Reference Examples 1 and 2. It should be noted that the kneading conditions are as follows.
[0166] [Mixing conditions]
[0167] Twin-screw extruder: diameter 32 mm, L / D = 56 (manufactured by Japan Steel Works, Ltd.)
[0168] Extruder set temperature: C2 / C3 / C4 / C5 / C6 / C7 / C8 / C9 / C10 / C11 / C12 / C13 / C14 / C15 / C16 / D = 100 / 170 / 210 / 220 / 220 / 220 / 220 / 220 / 220 / 220 / 220 / 220 / 220 / 220 / 220 / 220 / 220℃
[0169] Screw speed: 270rpm
[0170] Discharge: 25kg / hour
[0171] Wire material cooling: water cooling distance 40cm
[0172] Extrusion speed: 25m / min
[0173] Mould: 4 holes
[0174] The resin compositions of Examples 1 to 15, Comparative Examples 1 to 7, and Reference Examples 1 and 2 prepared above were used to evaluate pellet shape, amount of eye mucus, coloration, biomass, and MFR under the following conditions. The results are shown in Tables 1 and 2 described below.
[0175] 〔Pellet shape〕
[0176] The shapes of the obtained pellets were observed with a microscope (optical microscope) and evaluated based on the following criteria.
[0177] [Evaluation criteria]
[0178] A (excellent): The pellet shape is very good.
[0179] B (very good): The pellet size is uniform, but the surface roughness (shark skin) and poor cutting are slightly visible.
[0180] C (poor): There are many defects, cracks, rough surface (shark skin), and poor cutting of the pellets.
[0181] 〔Amount of eye discharge〕
[0182] The resin composition was fed to a twin-screw kneader at a rate of 25 kg / hour using a gravimetric feeder. The amount of eye discharge generated when 5 kg was discharged was sampled, the weight was measured, and evaluation was performed based on the following criteria.
[0183] [Evaluation criteria]
[0184] A (very good): The total weight of the generated eye mucus is 0.1 g or less.
[0185] B (poor): The total weight of the mucus is greater than 0.1 g.
[0186] 〔Coloring Evaluation (YI)〕
[0187] The YI (ASTM D1925) of the obtained pellets was measured using a spectrophotometer "CM-3500d" manufactured by Konica Minolta, Inc. (light source: D65, CM-A120 white calibration plate, CM-A126 petri dish set, regular reflection measurement SCE, measurement diameter ). About 5 g of the sample is filled in a petri dish and evenly spread, and the measurement is performed in this state to calculate the YI. The larger the value of the YI, the more yellow the resin composition is colored.
[0188] 〔Biomass degree〕
[0189] The biomass content of each resin composition was calculated by the following formula.
[0190] Biomass degree (weight %) = M3 / M4×100
[0191] In the above formula, M3 is the total weight of the bio-polyethylene resin used, and M4 is the total weight of the resin used.
[0192] 〔MFR〕
[0193] The MFR (g / 10 minutes) of the obtained pellets was measured under the conditions of a temperature of 210° C. and a load of 2160 g.
[0194] [Table 1]
[0195]
[0196] ※ Parts by weight relative to 100 parts by weight of the total of polyethylene resin (A) and EVOH (B)
[0197] [Table 2]
[0198]
[0199] ※ Parts by weight relative to 100 parts by weight of the total of polyethylene resin (A) and EVOH (B)
[0200] The resin composition of the embodiment having a low-density bio-polyethylene resin (A) and EVOH (B) at a specific ratio and containing component (C) can suppress the deterioration of the pellet shape and can also suppress the occurrence of eye spots and discoloration during molding, etc., which can reduce the appearance degradation.
[0201] On the other hand, the resin compositions of Comparative Example 1 not containing component (C) and Comparative Examples 2 and 6 in which the content of low-density bio-polyethylene resin (A) is greater than the range specified in the present invention have poor pellet shape or high YI and poor appearance.
[0202] In addition, the resin compositions of Comparative Examples 3 and 7 in which the content of the low-density bio-polyethylene resin (A) was less than the range specified in the present invention, and Reference Examples 1 and 2 in which petroleum-derived polyethylene was used, had high YI and poor appearance.
[0203] Furthermore, the resin compositions of Comparative Example 4 using a linear low-density polyethylene and Comparative Example 5 using a high-density bio-polyethylene caused a large amount of eye discharge.
[0204] The above embodiments show specific aspects of the present invention, but the above embodiments are merely examples and are not to be construed as limiting. Various modifications obvious to those skilled in the art are intended to be within the scope of protection of the present invention.
[0205] Industrial Applicability
[0206] The resin composition of the present invention can suppress the deterioration of pellet shape even when bio-polyethylene is used, and can suppress the occurrence of eye mucus and deterioration of appearance such as discoloration during molding. Therefore, the film, sheet, and stretched film formed from the resin composition of the present invention are useful as materials for various packaging containers.
Claims
1. A resin composition, characterized in that The invention comprises: a low-density bio-polyethylene resin (A); an ethylene-vinyl alcohol copolymer (B) having an ethylene content of 20 to 60 mol %; and at least one component (C) selected from the group consisting of an ethylene-vinyl acetate copolymer, an acid-modified polymer, and an ethylene-vinyl alcohol copolymer having an ethylene content of 70 to 90 mol %, wherein the low-density bio-polyethylene resin (A) is a low-density bio-polyethylene resin other than a linear low-density bio-polyethylene resin, and the weight ratio of the component (A) to the component (B) is 10 / 90 to 49 / 51. The acid-modified polymer is obtained by bonding an unsaturated carboxylic acid or anhydride thereof to a polymer by an addition reaction and / or a graft reaction, and the polymer is one or more selected from the group consisting of polyethylene, polypropylene, polybutene, and a copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms. The content of the component (C) is 0.1 to 20 parts by weight based on 100 parts by weight of the total of the component (A) and the component (B).
Citation Information
Patent Citations
Laminate film having layer containing plant-derived resin and package
JP2014104729A
Heat shrinkable multilayer film having layer containing resin derived from plant and method for producing the same
JP2014200968A
Synthetic resin blow-molded multilayer container including thick annular projection part in annular recess part and including surface layer containing plant-based ethylenic resin
JP2014213903A
Resin composition
CN114127167A
Resin composition, film using same, and multilayer structure
CN115348991A